Forecasting Firm Performance: Evidence from Romanian Furniture Firms - Hada, Teodor; Bărbuţă-Mişu, Nicoleta; Mărginean, Radu (Ekonomika, 2018)
The aim at this paper is to propose an econometric model for analyzing economic performance in the furniture industry in Romania, conducted on a sample of 293 firms. The net profit was considered as a dependent variable and the turnover, expenses with employees, value added, current liabilities and inventories as independent variables. Five hypotheses were proposed, tested and validated by using multiple linear regression. The most significant results show that there is a positive significant relationship between net profit and value added and a negative significant relationship between net profit and expenses with employees. Since the model has been validated statistically, we consider that it can provide useful predictions in terms of economic performance analysis in the furniture industry.Keywords: multiple linear regression, ANOVA, Durbin-Watson test, net profit estimation, value added
Keywords: multiple linear regression; ANOVA; Durbin-Watson test; net profit estimation; value added